Optimal Redistribution: Rising Inequality vs. Rising Living Standards - Axelle Ferriere; Philipp Grübener; Dominik Sachs (CESifo GmbH, 2024)
Over the last decades, the United States has experienced a large increase in, both, income inequality and living standards. The workhorse models of optimal income taxation call for more redistribution as inequality rises. By contrast, living standards play no role for taxes and transfers in these homothetic environments. This paper incorporates living standards into the optimal income tax problem by means of non-homothetic preferences. In a Mirrlees setup, we show that rising living standards alter both sides of the equity-efficiency trade-off. As an economy becomes richer, non-homotheticities imply a fall in the dispersion of marginal utilities, which weakens distributional concerns but has ambiguous effects on efficiency concerns. In a dynamic incomplete-market setup calibrated to the United States in 1950 and 2010, we quantify this new channel. Rising living standards dampen by at least 25% the desired increase in redistribution due to rising inequality.
Keywords: E62; H21; H31; O23; 330; taxation; growth; non-homothetic preferences; redistribution